Psycho-pedagogical conditions of the development of integrated individuality structures of teenagers with functional health disorders - G. U. Boyazitova (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the results of a systemic study into the conditions for efficient arrangement of psychological-pedagogic assistance to adolescents with functional health issues following the trends established in the psychological school of V.S. Merlin and V.V. Belous.